2024
DOI: 10.1039/d3tc03663d
|View full text |Cite
|
Sign up to set email alerts
|

Eulytite-type Ba3Yb(PO4)3:Tm/Er/Ho as a high sensitivity optical thermometer over a broad temperature range

Zonghao Lei,
Houhe Dong,
Lijie Sun
et al.

Abstract: Doping with Tm, Er, and Ho achieved blue, green, and red emission, respectively. BYP:Tm/Er/Ho achieved Sr > 0.63% K−1 over the temperature range of 303–603 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, it should be noted that these thermal sensitivity values are still low and hard to be further improved due to intrinsic confinement by the Boltzmann distribution theory. Importantly, recent works showed that some emissions from the nonthermally coupled energy levels of two lanthanides can overcome this issue for highly sensitive LIR-based temperature sensors. For instance, the design of the NaYF 4 :Yb/Nd@NaYF 4 @NaYF 4 :Yb/Er core–shell–shell nanostructure resulted in a high relative sensitivity of 9.6% K –1 due to the luminescence thermal enhancement of Nd 3+ and luminescence thermal quenching of Er 3+ with increasing temperature . However, at present, only several lanthanides can be used as dual emitters for the highly thermosensitive upconversion. Also, a simple codoping of the dual emitters in materials still showed low temperature sensitivity. So far, it has remained a challenge for the development of ultrasensitive nanothermometry based on nonthermally coupled upconversion systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that these thermal sensitivity values are still low and hard to be further improved due to intrinsic confinement by the Boltzmann distribution theory. Importantly, recent works showed that some emissions from the nonthermally coupled energy levels of two lanthanides can overcome this issue for highly sensitive LIR-based temperature sensors. For instance, the design of the NaYF 4 :Yb/Nd@NaYF 4 @NaYF 4 :Yb/Er core–shell–shell nanostructure resulted in a high relative sensitivity of 9.6% K –1 due to the luminescence thermal enhancement of Nd 3+ and luminescence thermal quenching of Er 3+ with increasing temperature . However, at present, only several lanthanides can be used as dual emitters for the highly thermosensitive upconversion. Also, a simple codoping of the dual emitters in materials still showed low temperature sensitivity. So far, it has remained a challenge for the development of ultrasensitive nanothermometry based on nonthermally coupled upconversion systems.…”
Section: Introductionmentioning
confidence: 99%
“…For UC luminescent materials used in optical thermometry, high-quality matrix crystals are one of the key elements to achieve accurate and efficient optical thermometers. 14–18 Fluoride matrix crystals (such as NaYF 4 , SrF 2 , LuF 3 , etc .) normally exhibit efficient UC luminescence due to their low phonon energy.…”
Section: Introductionmentioning
confidence: 99%